Analisis Pengaruh Perputaran Modal Kerja, Perputaran Kas, Perputaran Persediaan Terhadap Profitabilitas ( Pada Perusahaan Sektor Barang Konsumsi Yang Terdaftar Di Bei Tahun 2015-2020 ) - Sulastri, Sulastri (CV. ITTC INDONESIA, 2022)
This study aims to examine working capital turnover, cash turnover, inventory turnover on the profitability of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in the 2015-2020 period. The type of research used in this research is associative and descriptive research. The method used is purposive sampling with a sample of 9 companies during an observation period of 6 years so as to produce a total of 54 samples. The data collection technique used in this study is documentation. The data were analyzed using SPSS version 16 software. Judging from the results of the profitability T test, the value was 0.260> 0.05. This shows the results of the study that working capital turnover, cash turnover, inventory turnover have a simultaneous effect on profitability.